BCI-Based Consumers' Choice Prediction From EEG Signals: An Intelligent Neuromarketing Framework - Mashrur, Fazla Rabbi; Rahman, Khandoker Mahmudur; Miya, Mohammad Tohidul Islam; Vaidyanathan, Ravi; Anwar, Syed Ferhat; Sarker, Farhana; Mamun, Khondaker A. (Frontiers in Human Neuroscience, 2022)
Neuromarketing relies on Brain Computer Interface (BCI) technology to gain insight into how customers react to marketing stimuli. Marketers spend about $750 billion annually on traditional marketing camping. They use traditional marketing research procedures such as Personal Depth Interviews, Surveys, Focused Group Discussions, and so on, which are frequently criticized for failing to extract true consumer preferences. On the other hand, Neuromarketing promises to overcome such constraints. This work proposes a machine learning framework for predicting consumers’ purchase intention (PI) and affective attitude (AA) from analyzing EEG signals. In this work, EEG signals are collected from 20 healthy participants while administering three advertising stimuli settings: product, endorsement, and promotion. After preprocessing, features are extracted in three domains (time, frequency, and time-frequency). Then, after selecting features using wrapper-based methods Recursive Feature Elimination, Support Vector Machine is used for categorizing positive and negative (AA and PI). The experimental results show that proposed system achieves an accuracy of 84% and 87.00% for PI and AA ensuring the simulation of real-life results. In addition, AI and PI signals show N200 and N400 components when people tend to take decision after visualizing a product. Moreover, negative AA signals shows more dispersion than positive AA signals. Furthermore, this work paves the way for implementing such a neuromarketing framework using consumer-grade EEG devices in a real-life setting. Therefore, it is evident that BCI-based neuromarketing technology can help brands and businesses effectively predict future consumer preferences. Hence, EEG-based neuromarketing technologies can assist brands and enterprises in accurately forecasting future consumer preferences.